KARAKTERISTIK TANAH ANDISOL PADA LAHAN KERING DI DESA BATUNGSEL, KECAMATAN PUPUAN, KABUPATEN TABANAN UNTUK BUDIDAYA KOPI DAN SALAK - SUTYADNYANI, IDA AYU; MEGA, I MADE (Agrotrop : Journal on Agriculture Science; Vol 1 No 1 (2011), 2012)
The Characteristics of Andisol on Dryland at Batungsel Village, Pupuan District, Tabanan Regency for Growing Coffe and Salacca The purpose of the research was to know the characteristics of Andisol on dryland at Batungsel village, Pupuan District, Tabanan Regency for growing coffea and salacca plant. Soil survey methods and laboratory analysis were used in this research. The parameters of soil characteristics were observed i.e. soil morphology in the fields, physical and chemical, and mineralogical properties. Soil classification was done based on Soil Taxonomy system by using Keys to Soil Taxonomy (2003). Soil characteristics were: soil colour was dark bown, solum depth was deep (>100 cm),CEC was high, base saturation was high, and had a good soil fertility.Based on Soil Taxonomy system, the soil families were Typic Hapludands, ashy, isohyperthermic. The land suitability was suitable enough for coffea and salacca.
Keywords: andisol characteristics, land suitability, coffea, and salacca